Nutraceutics: Opening the Debate for a Framework for the Safety and Efficacy of Nutraceuticals Formulations - Mohammad Nadeem Khan; Ashok Kumar; Praveen Chand Dubey; Mohammad Rafi (Recent Trends in Infectious Diseases, 2023)
As of right now, there is no precise definition for nutraceuticals that distinguishes them from other food-based categories such herbal products, dietary supplements, pre- and probiotics, functional foods, and fortified foods. Several studies have shed light on the possible mechanisms of action of pharmaceutically active ingredients in food, emphasizing their ability to improve health, lower the risk of disease, and promote general wellbeing. However, Nutraceuticals confront difficulties in substantiating safety and health claims because national laws differ. It could be wise for national competent authorities to ask manufacturers to provide information on the safety, effectiveness, and mode of action for any claims made on product labels in order to address these issues, especially if the term "nutraceutical" is used. It might be possible to enhance the current regulatory environment by implementing such suggestions. Future developments in the creation of nutraceutical products may enhance toxicity, efficacy, and safety while offering a secure means of treating dangerous conditions. Despite the gaps in the current understanding of nutraceuticals, people need to change their mindset, prioritize concerns about drug interactions, side effects, and adverse reactions, and strive toward establishing a new paradigm of "Health for All" through creative dietary and lifestyle choices.
Keywords: Awareness; Lifestyles; Safety; life-threatening diseases; nutraceuticals; pharmacovigilance; traditional medicine